Nasal reconstruction: an analysis of a series of cases - Beatriz Buzzini Moura; Fernando Luiz Signore; Thaise Erani Buzzo; Luciano Portante Watanabe; Rinaldo Fischler; José Octávio Gonçalves de Freitas (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: Nasal reconstruction is challenging because of the central position and role of the nose in the face. Minor defects in this region become obvious. A retrospective analysis of 146 nasal reconstruction surgeries in the Integrated Plastic Surgery Services of the Ipiranga Hospital (SICP-HI) was performed, evaluating the incidence of nasal defects, as well as the main surgical techniques performed in accordance with each nasal region. METHODS: A retrospective descriptive study through a review of 109 medical records and photograph archives of patients treated in SICP-HI, São Paulo, SP, from January 2011 to June 2014. RESULTS: A total of 146 surgeries were performed. The mean patient age was 67 years. Regarding the type of malignant tumors found, 104 (73%) were basal cell carcinoma and 3 (2%) were squamous cell carcinoma. The remaining 36 (25%) lesions were benign. The most affected nasal regions were as follows: nasal wing, 55 (38%); the dorsum, 36 (25%); tip, 26 (18%); sidewalls, 12 (8%); unspecified, 7 (5%); total involvement of the nose, 5 (3%); and the columella, 2 (1%). There was a preference for primary closure of the defect. However, if this was infeasible, local flaps were used, in agreement with the literature. CONCLUSION: The nasal aesthetic subunits can be reconstructed using a variety of surgical techniques. The surgeon should seek an appropriate aesthetic and functional outcome.